Изначально у нас есть A(~B~C + ~BC + ~CB) + ~A(~B~C + B~C + BC)
Первый срок: A(~B~C + ~BC + ~CB)
= A(~B(~C + C) + ~CB)
= A(~B(True) + ~CB)
= A(~B + ~CB)
= A((~B + ~C)(~B + B))
= A((~B + ~C)(True))
= A(~B + ~C)
Второй срок: ~A(~B~C + B~C + BC)
= ~A(~C(~B + B) + BC)
= ~A(~C(True) + BC)
= ~A(~C + BC)
= ~A((~C + C) (~C + B))
= ~A((True) (~C + B))
= ~A(~C + B)
Итак First Term
+ Second Term
становится: ~A(~C + B) + A(~B + ~C)
= ~A~C + ~AB + A~B + A~C
= AxorB + ~A~C + A~C
= AxorB + ~C(~A + A)
= AxorB + ~C(True)
= AxorB + ~C
Следовательно, в итоге мы получим AxorB + ~C